DEVELOPING READING EXERCISES - ACHMAD FAIZIN; MOHAMAD HASYIM ASYARI (Fakultas Sastra Universitas Gresik, 2016)
This paper describes the steps in comprehending a text. The steps lead to developing the exercises that helped the students to understand a text easier. The instruction was designed based on the eight important micro skills. These micro skills in comprehending the reading text were hoped that such kind of exercises can give aid for the students to develop their understanding in the text.